Nasal airway evaluation in obstructive sleep apnoea patients: volumetric tomography and endoscopic findings - Rodrigues, M. M.; Gabrielli, M. F.R. [UNESP]; Garcia Junior, O. A.; Pereira Filho, V. A. [UNESP]; Passeri, L. A. (Elsevier, 2017)
Obstructive sleep apnoea (OSA) results from the recurrent collapse of the upper airway during sleep. Nasal abnormalities influence the stability of the pharynx. The aim of this study was to evaluate the volumetric and anatomical changes of the nasal cavity in patients with OSA. The Nasal Obstruction Symptom Evaluation (NOSE) scale was used to grade nasal obstruction. Sleep-related breathing disorders were evaluated by polysomnography. The nasal airway volume was obtained from computed tomography scans through volumetric reconstruction of the nasal airway. Alterations to the nasal anatomy were identified by nasal fibre-optic endoscopy. Ninety-four patient charts were analyzed. The final sample comprised 32 patients with severe OSA, 16 with moderate OSA, 23 with mild OSA, and 20 without OSA. Three groups were established based on nasal obstruction and OSA. The groups were compared for nasal airway volume (P = 0.464) and body mass index (P = 0.001). The presence of nasal septum deviation and inferior turbinate hypertrophy were related to the NOSE score (P = 0.05 for both), apnoea–hypopnoea index (P = 0.03 and P = 0.05, respectively), and nasal airway volume (P = 0.71 and P = 0.78, respectively). In this nasal airway evaluation of OSA patients, the presence of sites of obstruction was correlated with the severity of OSA; this was not the case for the evaluation of the nasal airway volume dimensions.
Keywords: nasal airway volume; nasal endoscopy; obstructive sleep apnoea